Effect of Batter Mix Variations on Sensory Quality of Breaded Shrimp - Farida, Iftachul; Khairunnisa, Anis (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
Vaname shrimp is one of the fishery products cultivated at Jembrana Marine and Fisheries Polytechnic with the potential to be developed as breaded shrimp (BS). The objective of this study was to determine the effect of batter mix (BM) on sensory quality of BS. There were three types variation of BM, i.e. mix of all-purpose instant flour:cold water (1:2; B1); mix of all-purpose instant flour:eggs (1:2; B2); mix of all-purpose instant flour:cold water:eggs (2:1:2; B3) with frozen (b) and fried (g) treatment. ANOVA were used to analyze the data, followed by Duncan’s additional tested for significant results. Sensory-hedonic tested showed that effect of BM variation did not significantly differ (p>0.05) on color, compactness, flavor, and overall attribute of frozen BS, as well as flavor, taste, texture, and overall sensory quality of fried BS. Different types of BM also did not show significantly difference on sensory-rating tested (p>0.05) for appearance, flavor, taste, and texture of fried BS. In this test, Bb1 attained first rank for appearance dan Bb3 attained first rank for color, compactness, flavor, and overall of frozen BS. Bg2 attained the first rank for appearance, flavor, texture, and overall attributes and Bg1 was the first rank for the taste attribute of fried BS.